Ecosystem Carbon and Nitrogen Accumulation after Grazing Exclusion in Semiarid Grassland - Qiu, Liping; Wei, Xiaorong; Zhang, Xingchang; Cheng, Jimin (PloS one, 2013)
The grazing exclusion in degraded grassland has been extensively used to prevent the loss of grassland resources and to improve grassland services. The effects of grazing exclusion on C and N balance, however, have not been well addressed but are essential for assessing grassland C sinks, the sustainable use of grassland resources and the support of grassland services. To understand the response of ecosystem C and N to grazing exclusion in semiarid grassland, we determined the C and N in litter, aboveground biomass, roots and soils from ungrazed grassland fenced at different times in northwest China. Our results showed that the aboveground biomass, root biomass and plant litter were 70-92%, 56-151% and 59-141% higher, respectively, in grazer excluded grassland than in grazed grassland. Grazing exclusion significantly increased C and N stored in plant biomass and litter and increased the concentrations and stocks of C and N in soils. Grazing exclusion thus significantly increased the C and N stored in grassland ecosystems. The increase in C and N stored in soil contributed to more than 95% and 97% of the increases in ecosystem C and N storage. The highest C and N stocks in ecosystems were observed in 17-year grazer excluded grassland. The results from this study indicate that grazing exclusion has the potential to increase C and N storage in degraded semiarid grassland and that the recovery of ecosystem C and N was mainly due to the accumulation of C and N in soils.